India-Maldives Relationship: Similarities of National Interest - Yadav, Baljeet; Kumar, Mukesh (Journal of Research in Innovative Teaching and Inclusive Learning, 2025)
The bilateral relationship between India and the Republic of Maldives represents a paradigmatic example of how geographical proximity, historical ties, and convergent national interests shape contemporary diplomatic engagement in the Indian Ocean region. This study examines the multifaceted dimensions of Indo-Maldivian relations, focusing on the convergence of national interests that has sustained their partnership despite periodic diplomatic challenges. Through comprehensive analysis of economic cooperation, security collaboration, and strategic alignment, this research demonstrates how both nations have navigated complex geopolitical dynamics while maintaining core shared objectives. The paper utilizes recent data from 2024-2025 to illustrate the resilience of bilateral ties, particularly following the diplomatic recalibration that occurred after initial strains in early 2024. The findings reveal that despite occasional divergences in approach, both countries maintain fundamentally aligned interests in maritime security, economic development, regional stability, and cultural preservation. This research contributes to the understanding of small state-large state dynamics in South Asian geopolitics and provides insights into how shared national interests can override temporary political disagreements to sustain long-term strategic partnerships.